Insecticide resistance mediated by an exon skipping event. Issue 22 (2nd November 2016) - Berger, Madeleine; Puinean, Alin Mirel; Randall, Emma; Zimmer, Christoph T.; Silva, Wellington M.; Bielza, Pablo; Field, Linda M.; Hughes, David; Mellor, Ian; Hassani‐Pak, Keywan; Siqueira, Herbert A. A.; Williamson, Martin S.; et al.
Abstract: Many genes increase coding capacity by alternate exon usage. The gene encoding the insect nicotinic acetylcholine receptor (nAChR) α6 subunit, target of the bio‐insecticide spinosad, is one example of this and expands protein diversity via alternative splicing of mutually exclusive exons. Here, we show that spinosad resistance in the tomato leaf miner, Tuta absoluta is associated with aberrant regulation of splicing of Ta α 6 resulting in a novel form of insecticide resistance mediated by exon skipping. Sequencing of the α6 subunit cDNA from spinosad selected and unselected strains of T. absoluta revealed all Ta α 6 transcripts of the selected strain were devoid of exon 3, with comparison of genomic DNA and mRNA revealing this is a result of exon skipping. Exon skipping cosegregated with spinosad resistance in survival bioassays, and functional characterization of this alteration using modified human nAChR α7, a model of insect α6, demonstrated that exon 3 is essential for receptor function and hence spinosad sensitivity. DNA and RNA sequencing analyses suggested that exon skipping did not result from genetic alterations in intronic or exonic cis ‐regulatory elements, but rather was associated with a single epigenetic modification downstream of exon 3a, and quantitative changes in the expression of trans ‐acting proteins that have known roles in the regulation of alternative splicing. Our results demonstrate that the intrinsic capacity of the α6 gene to generate transcript diversity via alternative splicing can be readily exploited during the evolution of resistance and identifies exon skipping as a molecular alteration conferring insecticide resistance.